(untitled) (Malaysian Journal of Civil Engineering, 2018)
Integral bridges have become one of the most common types of joint-less bridge construction, certainly over the last three decades. Simple integral abutments, such as stub-type abutments supported by piling, have been found to perform well and recommended for widespread use. Cost-effective system in terms of construction, maintenance and longevity becomes their principal advantages, derived from the elimination of expansion joints and bearings. Elimination of joints from bridges creates a significant soil-structure interaction behind the abutment. A 2D finite element analysis was performed on a typical integral abutment bridge using OASYS SAFE to investigate the complex interactions that exist between the stub-type integral abutment bridge and the backfill soil. Where possible, these results were validated with existing field data. The results from this analysis are believed to help answer two of the most debated issues with respect to stub-type integral abutment bridge-soil interaction analyses. Firstly, it is clear, and now possible, that a reliably accurate soil constitutive model is used in the analysis/design. The Mohr-Coulomb soil model was found to realistically represent the soil behaviour. Secondly, the research may suggest that cyclic movements / loads may not significantly influence the overall behaviour of integral abutment bridges especially in a small daily temperature changes.